(untitled) (aSSIST Business Review, 2026)
(1) Background/Purpose: The global railway vehicle market is expanding at a compound annual growth rate of approximately 4.3%, reaching approximately EUR 190 billion in 2021 and projected to grow further through 2026. Korea’s railway vehicle industry, while technically capable, has failed to convert domestic engineering strengths into sustained international market success. This study diagnoses the structural and strategic factors behind this gap and proposes the RAILS framework as a comprehensive strategy to enhance global competitiveness. (2) Methodology: The study combines qualitative case-study analysis (regional market surveys across Europe, Asia, North America, and emerging markets; case analyses of the Malaysia-Singapore High-Speed Rail project failure; and competitive benchmarking of Siemens, Alstom, CRRC, Stadler, and Hitachi Rail), with quantitative market data from SCI Verkehr and ARUP industry reports and SWOT analysis. Five strategic pillars are developed from this evidence base. (3) Findings: Korea’s competitive disadvantage stems from: (i) inadequate regional localization and modular platform architecture; (ii) slower adoption of AI, digital twin, and IoT-based operational systems; (iii) a lagging eco-technology portfolio (hydrogen, battery) relative to Alstom and Siemens; (iv) weak global after-sales service infrastructure; and (v) insufficient strategic packaging of financial support, technology transfer, and operational services in international bids, as illustrated by the loss of the Malaysia-Singapore HSR project. The RAILS strategy—Regional Customization, AI-Driven Digitalization, Innovation for Sustainability, Lifecycle Maintenance, and Strategic Global Partnerships—addresses each of these gaps. (4) Originality/Value: RAILS integrates Porter’s value chain and Rappaport’s shareholder value principles into a sector-specific, actionable strategic framework for Korean railway vehicle exporters. The framework provides a structured roadmap applicable to emerging market entry in Southeast Asia, Africa, and the Middle East.